Elements that students perceive as a mathematics teacher in the configuration of their professional identity. - Rivera Abrajan, Magdalena (2024)
In recent decades, there has been extensive research into the identity of teachers, with a particular focus on early education teachers. However, there is a noticeable gap in research regarding the formation of the identity of mathematics teachers during their professional training. The main objective of this article is to present the significant elements in the formation of professional identity, as perceived from the perspective of students, highlighting the aspects they consider important in their university education.This study adopts a qualitative and exploratory approach. The collection of narratives took place during the period from February to March 2020. Eleven students who comprised the final semester of the bachelor’s degree program in Mathematics at the Universidad Autónoma de Guerrero, Mexico, were invited to participate in the research. Data collection was carried out through the writing of a school narrative, which covered nearly four years of their university experience, as well as some episodes from their prior education. In addition, group interviews were conducted via video conference due to the COVID-19 health emergency. Data analysis was performed using a thematic analysis approach, resulting in the identification of four categories that, in turn, grouped eleven significant themes for students in the formation of their professional identity. This study concludes that analyzing the experiences lived by students, as narrated in their narratives, provides valuable insight into their professional identity. It delves into how they perceive and express their identity in relation to other professionals in training, as well as how they attribute meaning to their experiences and integrate them as a fundamental part of their journey to becoming educators.